Comparison of Germ Patterns and Antimicrobial Susceptibility in Chronic Suppurative Otitis Media with Cholesteatoma and without Cholesteatoma in Dr. Mohammad Hoesin Hospital. - Ahmad Hifni; Rian Hasni; Fiona Widyasari; Abla Ghanie; Erial Bahar (HM Publisher, 2021)
Introduction: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the middle ear and mastoid cavity. It is necessary to identify bacterial patterns and antibiotics susceptibility in CSOM. Appropriate administration of antibiotics is essential to treat infection and prevent widespread resistance. Objective: The aim of this study is to compare the pattern of germs and antibiotic susceptibility between CSOM with cholesteatoma and without cholesteatoma. Methods: Observational study with cross-sectional design. Data collection was carried out using medical record data on 102 subjects who underwent middle ear swab and bacterial culture from January to December 2019. Results: From 102 subjects and 122 bacterial culture results. it was found that Pseudomonas aeruginosa (36.1%) was one of the most common organisms to cause CSOM. followed by Staphylococcus haemolyticus. Staphylococcus epidermidis and Staphylococcus aureus. There was a significant difference between the germ pattern and the type of CSOM (p = 0.002). Amikacin. meropenem. gentamicin. cefepime. ciprofloxacin and ceftazidime were found to be the most effective antibiotics for Pseudomonas aeruginosa. The rate of resistance to tigecycline and cefazoline were highest. Age. sex. nutritional status and comorbidities were not factors that significantly influenced the incidence of cholesteatoma in CSOM. Conclusion: There is a significant difference between the germ pattern in both CSOM groups. Patients that show Gram negative have a significant effect on the incidence of CSOM with cholesteatoma.